Proceedings of the Fifth International Conference on Tangible, Embedded, and Embodied Interaction 2010
DOI: 10.1145/1935701.1935744
|View full text |Cite
|
Sign up to set email alerts
|

Sensing through structure

Abstract: We present an approach to designing input devices that focuses on the structure of materials. We explore and visualize how a material reacts under manipulation, and harness the material's properties to design new movement sensors. Two benefits spring out of this approach. One, simpler sensing emerges from making use of existing structure in the material. Two, by working with the natural structure of the material, we create input devices with readily recognizable affordances. We present six projects using this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Not only does Disney shy away from promoting many of the technologies employed to achieve objectives associated with their tracking agenda, but they frame many of these systems using somewhat defensive language within their attempts to convince visitors of the advantages and fend off criticism from media sources. For example, Disney has never explicitly blogged about step trackingwhich is done through MagicBands 13or embedded sensors within floors or walkways, yet various sources, including publications by Disney "imagineers," assert they engage in these practices and have tested a number of different approaches (e.g., Andrews et al 2016;Slyper, Poupyrev, and Hodgins 2010). Instead, Disney glosses over them, while introducing the features or attractions that these forms of tracking support, mentioning the underlying technologies only in the vaguest terms, yet with highly positive language and framing.…”
Section: Action Arena 4: Guest Trackingmentioning
confidence: 99%
“…Not only does Disney shy away from promoting many of the technologies employed to achieve objectives associated with their tracking agenda, but they frame many of these systems using somewhat defensive language within their attempts to convince visitors of the advantages and fend off criticism from media sources. For example, Disney has never explicitly blogged about step trackingwhich is done through MagicBands 13or embedded sensors within floors or walkways, yet various sources, including publications by Disney "imagineers," assert they engage in these practices and have tested a number of different approaches (e.g., Andrews et al 2016;Slyper, Poupyrev, and Hodgins 2010). Instead, Disney glosses over them, while introducing the features or attractions that these forms of tracking support, mentioning the underlying technologies only in the vaguest terms, yet with highly positive language and framing.…”
Section: Action Arena 4: Guest Trackingmentioning
confidence: 99%
“…More recently, conductive flament has been used to detect object deformation. While prior research created deformation sensors by casting silicone [8,35] or attaching copper tape to shear structures (Foldio [21]), researchers showed that deformation sensing can also be achieved by printing parts of the object with conductive flament (Flexibles [30]).…”
Section: Adding Sensing To 3d Printed Objectsmentioning
confidence: 99%
“…Deformation sensing can be achieved by embedding sensors into objects [27,47,53,49,30,48] or using optical sensing [12,9,46,45,33,54]. Other approaches employ resistive [44,10,1], capacitive [28], or piezoelectric [35,36] sensing.…”
Section: Deformation Sensingmentioning
confidence: 99%
“…Probably most closely related to our approach is work by Slyper et al [44] and more recently Bächer et al [1]. Slyper et al embed wires inside manually fabricated soft silicone objects of varied geometry to resistively or magnetically sense versatile interactions, including bending, twisting, pressing, and stretching.…”
Section: Deformation Sensingmentioning
confidence: 99%
See 1 more Smart Citation